Dual Effects of N, N-dimethylformamide on Cell Proliferation and Apoptosis in Breast Cancer. Issue 4 (5th December 2017) - Zhang, Jihong; Zhou, Daibing; Zhang, Lingyun; Lin, Qunbo; Ren, Weimin; Zhang, Jinguo; Nadeem, Lubna; Xu, Guoxiong
N, N-dimethylformamide (DMF) has been widely used as an organic solvent in industries. DMF is a potential medication. However, the antitumorigenic role of DMF in breast cancer remains unclear. Here, we examined dose-dependent effects of DMF on proliferation and apoptosis in breast cancer MCF-7 and nontumorous MCF-12A cells. We found that DMF had a growth inhibitory effect in MCF-12A cells in a dose-dependent manner. By contrast, however, DMF had dual effects on cell proliferation and apoptosis in MCF-7 cells. DMF at a high dose (100 mM) significantly inhibited MCF-7 cell growth while at a low dose (1 mM) significantly stimulated MCF-7 cell growth (both P < .05). The inhibitory effect of DMF on cell proliferation was accompanied by the decrease of cyclin D1 and cyclin E1 protein expression, leading to the cell cycle arrest at the G0/G1 phase. Furthermore, a high-dose DMF significantly increased the number of early apoptotic cells by increasing cleaved caspase-9 and proapoptotic protein Bax expression and decreased the ratio of Bcl-xL/Bax ( P < .01). Thus, our data demonstrated for the first time that DMF has dual effects on breast cancer cell behaviors depending upon its dose. Caution must be warranted in determining its effective dose for targeting breast cancer.